'Des Yeux Qui Ne Voient Pas...': The smartphones - Luca Di Lorenzo (Footprint)
Three of the most influential chapters of Le Corbusier’s Vers une Architecture are collected under the common title ‘Des yeux qui ne voient pas…’ (Eyes which do not see…). Liners, airplanes, and automobiles are shown as the expression of the powerful beauty of practical form: honest, simple, functional and technological. These very famous pages remind us that form is not only derived from precise typological choices or from reasoned morphogenetic diagrams, but it could also be a direct expression of the Kunstwollen.